KOMPARASI KINERJA ALAT TANAM JAGUNG DAN TUGAL PADA LAHAN KERING KABUPATEN SIGI SULAWESI TENGAH - Anugerah Fitri Amalia; Heni SP Rahayu; Muchtar (Jurnal Agritechno, 2020)
One of the efforts to accelerate the achievement of corn self-sufficiency is the efficiency of farming through the use of agricultural machinery. The use of agricultural machinery at the farm level especially in planting and fertilizingis still scarcely done, while the availability of agricultural labor is decreasing recently. Innovations will be adopted by farmers based on its performance in the field which should be applicable and efficient. The study aims to determine the performance of seed planters as planting and fertilizing tool on dry land in Sigi Regency. The research method uses agro technical studies that measure theoretical work capacity (Kt), actual work capacity (Ka), as well as the efficiency of seed planter and tugal performance. The results shows that seed planter’s performance is higher than tugal. The seed planter has an average theoretical field capacity 1.92 ha/hour with an advanced speed of 6.42 km/hour and has an actual field capacity 0.625 ha/hour, whiletugal toolhas theoretical capacity 0.50 ha/hour with an average actual field capacity 0.167 ha/hour. However, the accuracy of the volume of seed and fertilizer fallfrom the seed planter have to be improved.